Cerebral hyperperfusion syndrome after carotid angioplasty - Miloševič, Zoran (Radiology and oncology (Ljubljana), 2002)
Background. Cerebral hyperperfusion syndrome after carotid endarterectomy is an uncommon but well-de- fined entity. There are only few reports of "hyperperfusion injury" following carotid angioplasty. Case report. We report an unstable arterial hypertension and high grade carotid stenosis in a 58-year-old, right-handed woman. After a stroke in the territory of middle cerebral artery carotid angioplasty was per- formed in the patient. Among riskfactors, the long lasting arterial hypertension was the most pronounced. Immediately after the procedure, the patient was stable without any additionalneurologic deficit. The sec- ond day, the patient had an epileptic seizure and CT revealed a small haemorrhage in the left frontal lobe. Conclusions. The combination of a high grade carotid stenosis and unstable arterial pressure is probably an important prognostic factor in the pathogenesis of hyperperfusion syndrome.
Keywords: Adverse Effects; Angioplastika; Angioplasty; arterije; Carotid Artery Diseases; Cerebral Hemorrhage; cerebrovaskularne bolezni; Complications; Glavobol; Headache; Hipertenzija; Hypertension; Karotidna arterija, bolezni; Middle Age; Možganska krvavitev; Napadi krčev; ožilje; Reperfusion Injury; Reperfuzijska poškodba; Seizures; Srednja leta; Surgery; therapy; zdravljenje